Radiation-Enhancement Properties of an X-Band Woodpile EBG and Its Application to a Planar Antenna. (21st January 2014) - Frezza, Fabrizio; Pajewski, Lara; Piuzzi, Emanuele; Ponti, Cristina; Schettini, Giuseppe
Abstract : A woodpile Electromagnetic Bandgap (EBG) material has been designed, by using an in-house code that implements the Fourier Modal Method (FMM). A couple of alumina-woodpile samples have been fabricated. Several results have been collected for the transmission behaviour of the woodpile and of resonators with woodpile mirrors, in a shielded anechoic chamber, by using a vector network analyzer, in the 8–12 GHz range. These new experimental data highlight interesting properties of 3D EBG resonators and suggest possible innovative applications. Comparisons of the collected results with FMM show a satisfactory agreement. An application of the EBG resonator has been considered, for gain enhancement of a microstrip antenna: an increase of about 10 dB in the broadside gain has been measured; experimental data and numerical results obtained with the commercial software HFSS show a good agreement. A comparison is presented between EBG resonator antennas and two-dimensional uniform arrays. Finally, HFSS results are provided for EBG resonator antennas working at higher frequencies or with a more selective superstrate: a gain enhancement of more than 18 dB is achieved by such antennas.